2017
DOI: 10.1590/s1677-5538.ibju.2016.0484
|View full text |Cite
|
Sign up to set email alerts
|

The prostate after castration and hormone replacement in a rat model: structural and ultrastructural analysis

Abstract: Purpose:To evaluate if late hormonal replacement is able to recover the prostatic tissue modified by androgenic deprivation.Materials and Methods:24 rats were assigned into a Sham group; an androgen deficient group, submitted to bilateral orchiectomy (Orch); and a group submitted to bilateral orchiectomy followed by testosterone replacement therapy (Orch+T). After 60 days from surgery blood was collected for determination of testosterone levels and the ventral prostate was collected for quantitative and qualit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 49 publications
0
8
0
Order By: Relevance
“…Nonetheless, the reduction observed on the size of the prostate gland after castration, along with the decrease of animal's body weight, indirectly reflects the loss of TES activity of over the prostate gland thus, implicitly validating the model. Androgen deprivation is known to impact specific regions of prostate tissue, namely, the acinar epithelium, the number of mast cells and collagen fibers 24 .…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, the reduction observed on the size of the prostate gland after castration, along with the decrease of animal's body weight, indirectly reflects the loss of TES activity of over the prostate gland thus, implicitly validating the model. Androgen deprivation is known to impact specific regions of prostate tissue, namely, the acinar epithelium, the number of mast cells and collagen fibers 24 .…”
Section: Discussionmentioning
confidence: 99%
“…This finding coincided with other studies which reported marked thickening of the extracellular matrix of the prostate gland with increased collagen deposition and hypertrophied smooth muscle cells in diabetic and castrated rats. These stromal changes were attributed to androgen depletion and were explained by being an attempt to preserve the integrity of the glandular epithelium and the secretory process [9,29,30] . In addition, this increase in the stromal elements of diabetic prostate would induce a reactive stromal microenvironment that may lead to proliferation, cell migration and pathological processes.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the mast cells, they have recently been postulated as an important marker for the prognosis of prostate cancer and a possible target for immune therapies (Johansson et al, ; Taverna et al, ). Despite the scarce data evaluating the influence of testosterone on mast cells, Felix‐Patrício et al () showed that castration induced an increase of 528% in mast cell number in rat ventral prostate, which was knocked down after testosterone replacement. Associated with inflammation, oxidative stress in an essential factor for the initiation of prostate cancer (Gupta‐Elera et al, ).…”
Section: Discussionmentioning
confidence: 99%